Efficacy of Different Primaquine Regimens to Control Plasmodium falciparum Gametocytemia in Colombia (2017)
ABSTRACT: Treatment against Plasmodium falciparum malaria includes blood schizonticides to clear asexual parasites responsible for disease. The addition of gametocytocidal drugs can eliminate infectious sexual stages with potential for transmission and the World Health Organization recommends a single dose (SD) of primaquine (PQ) to this end. The efficacy of PQ at 0.75 mg/kg to suppress gametocytemia when administered in single or fractionated doses was evaluated. A clinical controlled study with an open-label design was executed; three groups of 20 subjects were studied sequentially. All subjects were treated with the standard dose of artemether–lumefantrine plus the total dose of 0.75 mg/kg of PQ administered (without previous G6PD testing) in three different ways: Group “0.75d-3” received 0.75 mg/kg on day 3; Group “0.50d-1 + 0.25d-3” received 0.50 mg/kg on day 1 and 0.25 mg/kg on day 3; Group “0.25d-1,2,3” received 0.25 mg/kg on days 1, 2, and 3. Subjects were evaluated on days 1, 4, and 7 by thick smear microscopy and quantitative polymerase chain reaction to determine the carriage of immature and mature gametocytes. There were no adverse events. The three schemes caused a marked reduction (75–85%) in prevalence of gametocytes on day 4 compared with day 1, but only the group that received 0.75 mg/kg on day 3 maintained the reduced gametocyte burden until day 7. None of the three treatments were able to clear gametocyte carriage on days 4 or 7, but the group that received the SD had the lowest prevalence of gametocytes (15%). Further studies are needed to establish a PQ regimen with complete efficacy against gametocytes.